Industrial Devon: Reflections and learning from schools-based heritage outreach in Scotland. Issue 3 (3rd July 2019) - Mills, Catherine; Simpson, Ian; Geller, Jennifer
ABSTRACT: 'Industrial Devon' is a schools-based heritage engagement initiative that staff at the Centre for Environment, Heritage and Policy at Stirling University, Scotland, undertook in 2013/14. The project's implementation involved collaboration with a variety of internal and external education and municipal partners, together with student volunteers. The project explored the environmental history of historic industries located along the River Devon in Clackmannanshire, Scotland, and the associated settlements along its route through the 'eyes' and activities of the local primary school pupils. The year-long project offered a hands-on, experiential approach to knowledge exchange delivery in schools; supplementing the state curriculum and research design for promoting local heritage across community groups of all ages and locations. The reflective narrative on how the initiative evolved, examines the pitfalls and opportunities encountered during planning and implementation and is designed both to inspire and provide a practical tool kit to all considering embarking on similar activities.